450 Minimally Invasive Multiple-Rod Constructs With Robotics Planning in Adult Spinal Deformity Surgery: A Case Series. (1st April 2022) - Shah, Vrajesh; Pham, Martin H.; Diaz-Aguilar, Luis D.; Lehman, Ronald A.
Abstract : INTRODUCTION: Multiple rod constructs (MRCs) are often used in adult spinal deformity correction for increased stability and rigidity. There are currently no reports showing minimally invasive robotic multi-rod long-segment posterior fixation and its technical feasibility through preoperative software planning. METHODS: Data was collected retrospectively from medical records of 6 consecutive patients who underwent minimally invasive multiple-rod constructs with robotics planning by a single surgeon at an academic center between March-August 2020. RESULTS: A total of 6 patients (4 females, mean age 69.7 years) underwent minimally invasive long-segment (6+) posterior fixation with multiple rods (3+) using the Mazor X Stealth Edition robotics platform. Average follow-up was 9.3 months. All patients underwent oblique lumbar interbody fusion as a first stage, followed by second stage posterior fixation in the same day. The mean number of levels posteriorly instrumented was 8.8. One patient underwent 3 rod fixation (1 iliac, 2 S2AI) and 5 patients underwent quad rod fixation (2 iliac, 2 S2AI). The mean time to secure all rods was 8 minutes 36 seconds. Mean improvement in spinopelvic parameters was -4.9 cm sagittal vertical axis, 18.0° lumbar lordosis, and -10.7° pelvic tilt with an average pelvic incidence of 62.5°. Mean EBL was 200 cc with no blood transfusions, and all but one patient ambulated on postoperative day 1 or 2. CONCLUSION: The preoperative software planning required of spinal robotics allows for not just the accurate placement of each pedicle screw in isolation, but the fine-detailing of an entire spine construct design. This concept is demonstrated in this case series where rod placement in a minimally invasive approach depends upon the preoperative design of the whole construct. Spinal robotics brings us into this new era of minimally invasive construct design. To our knowledge, this is the first description of the technical feasibility of multiple-rod constructs in minimally invasive adult spinal deformity surgery.